Penerapan Nilai Spiritual Dalam Tradisi Kenduri Hari Raya Sebagai Wujud Kearifan Lokal Pasca Pandemi (Studi Fenomenologis di Desa Sendang Jambon Ponorogo) - Umro'atin, Yuli; Nurcahyaningtias, Novia Dwi (Jurnal Penelitian, 2022)
The outbreak of the Corona virus (Covid-19) has changed religious practices in the life of the Muslim community. Religious practices are now changing and adapting according to different health protocols from the previous situation. Religious adherents are no longer in conflict with the lusts and disturbances of the devil and all kinds of things, but now have to deal with a deadly virus in performing religious rituals. Islam has invited mankind to follow the teachings in the Qur'an in a wise manner, good words, and clear exchange of ideas. This principle emphasizes that the spread of Islam must be carried out taking into account the situation and conditions of the community concerned, as exemplified by the Prophet Muhammad SAW. The type of research used is qualitative research with a phenomenological study approach, namely an approach that tries to explain or reveal the meaning of concepts or phenomena of experience based on the awareness that occurs in several individuals. Collecting data through observation, interviews and documentation. Checking the validity of the data with the triangulation method. The results of the study: (1) The tradition of festive feasts in the village of Sendang Jambon Ponorogo has existed since the time of the ancestors, namely around the 1940s, before Indonesia's independence. (2) The tradition of celebrating Eid al-Fitr and Eid al-Adha has become a routine for the residents of Sendang village, the majority of which are Nahdliyin people. The tradition is carried out on the night of the feast or called megengan, and in the morning after carrying out the 'Id prayer, by bringing tumpeng rice and giving lectures and prayers together. (3) The spiritual value in the kenduri tradition is carried out as a form of public gratitude for the coming of Muslim holidays, friendship, maintaining unity and integrity, mutual cooperation, giving alms, etc.